Wawasan Berbasis Gender terhadap Niat Berkelanjutan dalam Penggunaan Aplikasi Kesehatan Seluler di Indonesia: Studi Pascapandemi tentang Persepsi Ancaman Penyakit dan Efikasi Diri - Dewi, Citra Kusuma; Saputri, Marheni Eka; Sadewa, Devanka Elang (Fakultas Seni Rupa dan Desain ITB, 2025)
The sustained use of mobile health applications (mHealth) in the post-pandemic era is increasingly relevant due to ongoing health concerns and perceived disease threats (PDT). This study addresses significant gaps in understanding how self-efficacy and gender differences influence continuance intention (CI) to use mHealth applications. Guided by the Protection Motivation Theory (PMT), the research examines therelationships between PDT, self-efficacy, and CI, with gender as a moderating variable. Data from 415 mHealth users in Indonesia were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that PDT significantly influences CI, while self-efficacy directly enhances CI. Gender moderates the PDT-CI relationship, with female users showing a stronger connection. However, self-efficacydoes not mediate the PDT-CI relationship. The study highlights practical implications for mHealth developers, including the need for user-friendly and gender-sensitive designs to enhance self-efficacy and engagement. Limitations include the cross-sectional design and focus on Indonesian users, suggesting future research should adopt longitudinal approaches and explore diverse demographic and cultural contexts. The findings extend PMT's theoretical application and provide actionable insights for improving mHealth application adoption and retention in diverse populations.